RELATED PARTIESâ TRANSACTION AND EARNINGS MANAGEMENT: A CASE IN INDONESIA - Sumiyana, Sumiyana; Febrianto, Rahmat (Journal of Indonesian Economy and Business, 2012)
This study investigates the association between related partiesâ transactions andÂ earnings management in Indonesia. Firms executives officers accompanied by board ofÂ director members usually engage in related partiesâ transactions to expropriate the firmâsÂ resources. Therefore, they have incentives to manage earnings either to increase theirperquisites or possibly to mask such expropriation.This study presents evidence that earnings management is positively associated withÂ certain types of related partiesâ transactions. Overall, this study concludes that concernsabout related partiesâ transactions as a factor associated with earnings management areÂ warranted, especially for certain related partiesâ transactions. There are purchase costsÂ from subsidiary or parent companies and expenses incurred from the firmâs relatedÂ partiesâ transactions.Keywords: related partiesâ transactions, perquisite, earnings management.Â